INOVASI PEMBELAJARAN ARITMATIKA SOSIAL DENGAN PENDEKATAN PROJECT-BASED LEARNING BERBASIS ASET SEKOLAH DAN INTEGRASI LINTAS PELAJARAN - Eka Sariyanti; Ahmad Yani T (Universitas Bhinneka PGRI, 2025)
This study aims to explore the implementation of Project-Based Learning (PjBL) based on school assets in social arithmetic learning, and its impact on student engagement and understanding. This learning project involves the use of school gardens. where students are given the task of processing garden produce into products that can be sold, then analyzing the calculation of profit and loss. This study also involves cross-subject collaboration, especially with the subjects of Indonesian Language and Social Sciences (IPS). The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of PjBL based on school assets can increase students' motivation, engagement, and understanding of social arithmetic concepts. Cross-subject collaboration plays an important role in developing students' literacy and social entrepreneurship skills. This study also identified several challenges, such as time constraints in project management and students' difficulties in understanding the concept of calculating profit and profit margins. The implementation of PjBL contributes positively to developing 21st-century skills such as critical thinking, collaboration, and communication. This study concludes that the PjBL approach based on school assets and cross-subject integration is effective in improving the quality of social arithmetic learning, as well as providing contextual and meaningful learning experiences for students.